The impact of training on farmers’ human capital accumulation in rural China - Junxia Zeng; Lei Wan; Wenjin Long (PLoS ONE, 2026)
Training represents a crucial pathway for enhancing farmers’ human capital. China currently invests over 2 billion CNY (310 million USD) annually to train nearly a million professional farmers. While previous studies have primarily focused on the direct effects of training on production and income, there is no consensus on how training specifically contributes to farmers’ human capital accumulation. This study employs panel survey data from 753 farmers across four Chinese provinces collected in 2016 and 2019, utilizing Propensity Score Matching-Difference in Differences (PSM-DID) methodology to examine the impact of farmer training on participants’ human capital. The empirical analysis reveals that farmers who participated in professional training programs experienced significant improvements in their explicit human capital, demonstrated by increases of 6.76% and 13.30% in obtaining national vocational qualification certificates and farmer technical staff titles, respectively. Additionally, their internalized human capital showed marked enhancement, with increases of 21.03% and 11.29% in utilizing digital platforms such as WeChat groups and Douyin (or Kuaishou) for agricultural knowledge and skill acquisition. These findings suggest that China should continue prioritizing farmers’ human capital development, particularly through professional training programs, as a key strategy for promoting agricultural transformation and rural revitalization.